Phenology and suppression of stem weevils (Ceutorhynchus napi Gyllenhal and Ceutorhynchus pallidactylus Marsham) in oilseed rape in northern Serbia - Sivčev, Lazar; Sivčev, Ivan; Graora, Draga; Pešić, Snežana; Tomić, Vladimir; Dudić, Boris (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2018)
Stem weevils (Ceutorhynchus pallidactylus and Ceutorhynchus napi) are significant pests of oilseed rape that farmers regularly suppress by insecticide treatments intended against Brassicogethes aeneus. Recent studies have shown that in some regions of northern Serbia C. napi is dominant, while C. pallidactylus prevails in others. Increased damage from stem weevils has elicited an exploration of the situation and a study of their phenology and effects of insecticides in three differently managed fields: conventional, organic and integrated. New findings regarding the phenology of stem weevils show that both species were sporadically present in our experimental oilseed rape fields as early as during autumn (from the end of October 2010, BBCH 17-18). The main period of stem weevil settlement is the end of winter and early spring. Maximum flight of both weevil species was recorded on March 23 at the beginning of oilseed rape (OSR) stem elongation (BBCH 22-25), and one week later in the organic field. There were no significant differences in the number of settled weevils among the three differently managed fields. The insecticide treatment against C. napi was applied two weeks earlier than the usual treatment against B. aeneus and C. pallidactylus. Thus, it is clear that insecticide treatment directed against B. aeneus and C. pallidactylus is not effective against C. napi. In this way, such a practice can contribute to an increase in OSR damage, and density of the next generation of C. napi. A new generation of C. pallidactylus emerged from OSR fields in June 2011, while the majority of C. napi emerged in March of the following year.
Keywords: Stem weevils; Oilseed rape; Insecticides; Serbia